Time since onset might be of essence: A recommendation to assess the effects of combination of non-pharmacological neuromodulatory approaches at early stage since symptoms onset - Agostinho, Mariana; Weissman Fogel, Irit; Treister, Roi (Frontiers in Neurology, 2023)
In the past decade researchers began to assess the potential beneficial effects of non-invasive brain stimulation (NIBS) combined with a behavioral task as a treatment approach for various medical conditions. Transcranial direct current stimulation (tDCS) applied to the motor cortex combined with another treatment approach has been assessed as analgesic treatment in neuropathic and non-neuropathic pain conditions, and was found to exert only modest pain relief. Our group results show that combined tDCS and mirror therapy dramatically reduced acute phantom limb pain intensity with long-lasting effects, potentially preventing pain chronification. A review of the scientific literature indicates that our approach differs from that of others: We applied the intervention at the acute stage of the disease, whereas other studies applied the intervention in patients whose disease had already been established. We suggest that the timing of administration of the combined intervention is critical. Unlike in patients with chronic painful condition, in which the maladaptive plasticity associated with pain chronification and chronicity is well-consolidated, early treatment at the acute pain stage may be more successful in counterbalancing the not-yet consolidated maladaptive plasticity. We encourage the research community to test our hypothesis, both in the treatment of pain, and beyond.